Criminal Protection of Intellectual Security within Universities - Taha, Asst. Prof. Dr. Shaimaa Ibrahim Taha; Mahdi, Asst. Prof. Dr. Haider Abdul Jalil Mahdi (Sulaimani Journal for Humanities, 2026)
Security is considered one of the fundamental social needs of humans, as a person cannot live, sleep, or rest while struggling with fear or anxiety about a certain matter. Likewise, a person cannot lead a normal life while overwhelmed by fear, panic, or terror. Security and stability are the foremost requirements for humanity and an urgent necessity for any human endeavor. Achieving security in all its aspects, especially intellectual security, falls on the shoulders of all state institutions, including educational institutions such as universities. Universities play a vital and pivotal role in confronting threats to intellectual security and crimes that violate it, such as intellectual invasion and violent extremism leading to terrorism. This is because universities attract a large segment of society—students—and should be at the forefront in combating the deviation of thought through education and raising awareness about the danger of such ideas infiltrating the educational system. Ensuring and protecting intellectual security, and combating intellectual extremism and terrorism, require the promotion of a culture of positive thinking, encouraging constructive dialogue, acceptance of differing opinions, and purposeful intellectual discussions within classrooms—both among students and between students and university professors. Additionally, academic content should include topics that promote values of moderation, tolerance, coexistence, and peaceful living, alongside criminalizing acts that threaten intellectual security and addressing such deviant actions through legal texts that criminalize them. Given the above, universities have an important role in confronting intellectual extremism, as this is primarily an intellectual war. This war makes education a fertile ground for extremist forces to conduct their campaigns. These forces have worked, and continue to work, to penetrate and infiltrate the education sector by various means. From this perspective, our study on “Criminal Protection of Intellectual Security within Universities” gains importance. The university is an institution that plays a crucial role in shaping student behavior through its educational and pedagogical methods. It serves as the real gateway responsible for forming and reinforcing correct concepts in their minds, thereby achieving intellectual security and confronting extremism, which is a widespread phenomenon in societies that influences behaviors and may escalate into terrorism due to the interaction of many social, economic, and political factors. Through integrated efforts, universities will be able to effectively contribute to enhancing intellectual security in society at large and particularly within the university environment, safeguarding its members from violent and extremist intellectual deviations.
Keywords: Universities; Criminal Protection; Intellectual Security; Intellectual Extremism; Terrorism